Wage Dispersion and Search Behavior - Robert Hall; Andreas I. Mueller (Institute for the Study of Labor (IZA), 2015)
We use a rich new body of data on the experiences of unemployed job-seekers to determine the sources of wage dispersion and to create a search model consistent with the acceptance decisions the job-seekers made. From the data and the model, we identify the distributions of four key variables: offered wages, offered non-wage job values, the value of the job-seeker's non-work alternative, and the job-seeker's personal productivity. We find that, conditional on personal productivity, the dispersion of offered wages is moderate, accounting for 21 percent of the total variation in observed offered wages, whereas the dispersion of the non-wage component of offered job values is substantially larger. We relate our findings to an influential recent paper by Hornstein, Krusell, and Violante who called attention to the tension between the fairly high dispersion of the values job-seekers assign to their job offers – which suggest a high value to sampling from multiple offers – and the fact that the job-seekers often accept the first offer they receive.
Keywords: J31; J32; J64; 330; wage dispersion; reservation wages; search frictions; unemployment